1993
DOI: 10.1002/bip.360330115
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Induced conformational transition in xanthans with partially hydrolyzed side chains

Abstract: The conformational properties of xanthans with partially hydrolyzed side chains were investigated by optical rotation, CD, and differential scanning calorimetry (DSC). All variants displayed the well-known temperature-driven, cooperative order-disorder transition, and both optical rotation and DSC showed that the transition temperature was essentially independent of the content of terminal beta-mannose. It was found that up to 80% of the changes in the specific optical rotation accompanying the transition refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
5
9
1
Order By: Relevance
“…This suggests that the intact side chain (glucose residue) and the modified side chain (Figure 1) contribute differently to the total optical rotation, reflecting differences in the number of asymmetric carbons in the two cases (Jackson & Hudson, 1937). This finding parallels the observations for xanthan with partially hydrolysed (removed) side chains (Christensen, Knudsen, Smidsrød, Kitamura, Takeo, 1993), where the total optical rotation (and transition enthalpy) changed linearly with changes in the number of side chains. Secondly, it is noted that the transition temperatures obtained from OR agree well with those obtained by DSC, i.e.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 72%
See 1 more Smart Citation
“…This suggests that the intact side chain (glucose residue) and the modified side chain (Figure 1) contribute differently to the total optical rotation, reflecting differences in the number of asymmetric carbons in the two cases (Jackson & Hudson, 1937). This finding parallels the observations for xanthan with partially hydrolysed (removed) side chains (Christensen, Knudsen, Smidsrød, Kitamura, Takeo, 1993), where the total optical rotation (and transition enthalpy) changed linearly with changes in the number of side chains. Secondly, it is noted that the transition temperatures obtained from OR agree well with those obtained by DSC, i.e.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 72%
“…Chemical modifications of polysaccharide side chains generally influence such transition markers. For example, partial acid hydrolysis was used in a double helical polysaccharide, xanthan, to investigate the influence of the removal of side chains on the conformational transition of xanthan (Christensen, Knudsen, Smidsrød, Kitamura, Takeo, 1993). Since the order-disorder transition of schizophyllan is characteristic to the triple helical conformation (Kitamura & Kuge, 1989), it is necessary to investigate both of the molecular conformation and the transition behavior after the chemical modification.…”
mentioning
confidence: 99%
“…This is apparently contradicted by the observation that in the absence of the terminal mannose and consequently pyruvate there is still an increase in transition temperature with increasing salt content (Christensen, Knudsen, Smidsrød, Kitamura, & Takeo, 1993). Table 2 shows the values in the present work for the slope of the logarithm of the change in concentration divided by the change in reciprocal absolute transition temperature, compared with literature values.…”
Section: The Contrast Of the Effect Of Pyruvate And Glucuronic Acidcontrasting
confidence: 77%
“…As the salt might be expected to act similarly on both the glucuronic acid and the pyruvate groups, both having similar pKa values, the effect of the pyruvate can be viewed as superimposed upon but acting independently of the effect of glucuronic acid and the glucuronic acid effect becoming dominant when the pyruvate is removed. (Christensen, et al 1993) compared with values from the present work. Also shown are the results for the removal of the terminal mannose and slight reduction in glucuronic acid content.…”
Section: The Contrast Of the Effect Of Pyruvate And Glucuronic Acidmentioning
confidence: 78%
“…In order to estimate the DH vH , it is necessary to decide which slope should be selected. Christensen and his coworkers 48 reported that the van't Hoff plots of xanthan solutions showed two slopes below T ch , as found in the present study. They estimated DH vH from the data just below T ch (steep slope).…”
Section: Figuresupporting
confidence: 72%